Two centuries of changes in Andean crop distribution. (20th May 2021) - González‐Orozco, Carlos E.; Porcel, Mario
ABSTRACT: Aim: Historical changes in crop distributions of tropical regions are poorly understood and rarely quantified due to the scarcity of historical records. As early as 1796, Francisco José de Caldas recorded crop distribution and drew maps depicting crop regions for eight crops. Using Caldas' crop regions, we identify changes of crop distribution in relation to latitude and elevation, as well as compare their elevational limits over two centuries. Location: The northern Andean mountain range between Colombia and Ecuador. Taxon: Wheat, barley, potato, maize, sugarcane, cacao, plantain and cassava. Methods: We analysed Caldas' crop regions and compared them with a current homologous replication of the same crops. We tested whether elevational ranges and mean elevation of the crops varied between the colonial and contemporary periods and analysed the relationship between elevation and latitude. Results: In quantifying the historical and contemporary distributions, we identified a large expansion of 740.1 meters in the elevational range over 224 years for all eight crops. We also found crops located at lower latitudes south towards Quito distributed at a higher elevation. Main conclusions: Our findings use historical data never used before to investigate the evolution of crop distribution since the colonial period. Our analysis provides evidence to conclude that Caldas' work on climate and agriculture was essential to developing the field of tropical agriculture climatology, a discipline for which Caldas established but was never given recognition.